Upaya Guru Pendidikan Agama Islam dalam Pembentukan Karakter Peduli Lingkungan pada Siswa di SMPN 1 Bukittinggi - Arsil Arsil; Alimir Alimir; Jasmienti Jasmienti; Hamdi Abdul Karim (Lembaga Pengembangan Kinerja Dosen, 2023)
Environmentally Caring Character is an attitude and action that always strives to prevent damage to the surrounding natural environment, and develops efforts to repair natural damage that has occurred. Based on initial observations, the facts that the author found in the field are that there are still some students whose character is still far from what was expected, even though they have received PAI learning at school, such as there are still some students who like to throw rubbish carelessly, there are still some students who damage facilities. At school, there are still some students who are reluctant to be involved in cleaning the school environment and there are still some students who lack awareness in maintaining and maintaining gardens at school. The aim of this research is to determine the efforts of Islamic Religious Education teachers in forming environmentally caring character in class VIII students at SMPN 1 Bukittinggi and to describe the supporting and inhibiting factors in forming environmentally caring character in class VIII students at SMPN 1 Bukittinggi. The research in this thesis uses qualitative research. This research is descriptive qualitative field research as a research procedure that produces descriptive data in the form of written or spoken words from the people and behavior being observed. Based on the results of this research, it was found that the efforts of Islamic Religious Education teachers in forming students' environmentally caring character at SMPN 1 Bukittinggi were carried out in various ways, starting from the school principal's efforts in providing support and appreciation to students and parents, teachers' efforts in synchronizing learning materials with the character of caring for the environment, reminding students when someone behaves that does not reflect concern for the environment and modeling and providing an example to students. Supporting factors in the character education process at SMP N 1 Bukittinggi are good, namely the presence of pre-school experience, the existence of good learning motivation, the existence of students' attitudes and habits in learning, the teacher has the ability to deliver the material and can adapt it to the needs of the students, the teacher has high enthusiasm. in teaching. Meanwhile, the inhibiting factor: the bad habits of some students from home who are brought into the classroom, thus affecting other students.